Pengaruh Kecerdasan Emosional terhadap Prestasi Belajar Siswa Madrasah Ibtidaiyah - Sari, Ira; Azura, Wan; Utami, Sheila (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Student learning achievement is one of the indicators of the success of the educational process. However, achievement is not only determined by intellectual ability but also by emotional intelligence, which plays a role in managing emotions, building social relationships, and motivating oneself to learn. This study aims to analyze the influence of emotional intelligence on the learning achievement of elementary school students. The research method used is quantitative with a correlational approach. Data collection techniques were conducted through questionnaires to measure emotional intelligence and documentation of grades as indicators of learning achievement. The study population consists of all fifth-grade students totaling 22 students, and the sample was determined using purposive sampling. The research results show that the emotional intelligence of students is in the